2019
DOI: 10.1103/physrevmaterials.3.055603
|View full text |Cite
|
Sign up to set email alerts
|

Programmable filaments and textiles

Abstract: We analyze the various morphing structures obtained by actuating Janus filaments comprising driven and passive sectors and textiles incorporating driven and passive filaments. Transitions between alternative shapes and coexistence of absolutely stable and metastable states within a certain range of relative extension upon actuation are detected both in Janus rings and textiles. Both single filaments and textiles can be reverse designed to bend into desired shapes by controlling both the size and orientation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Tissue morphogenesis can inspire the design of such slender structures that change shape in a programmable way. Desired shapes can be attained by pre-patterning the internal structure, for example via metric change [10][11][12], controlled intrinsic curvature [13,14], prestress [15], or be self-organized, for example, through a propagating chemical reaction coupled with mechanical deformations [16][17][18][19]. The latter approach provides reconfigurable conformations in contrast with frozen-in patterns, and resembles the shape changes during morphogenesis with anisotropic deformations including different types of mechanical instabilities, such as creases, wrinkles, folds, and ridges [20].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue morphogenesis can inspire the design of such slender structures that change shape in a programmable way. Desired shapes can be attained by pre-patterning the internal structure, for example via metric change [10][11][12], controlled intrinsic curvature [13,14], prestress [15], or be self-organized, for example, through a propagating chemical reaction coupled with mechanical deformations [16][17][18][19]. The latter approach provides reconfigurable conformations in contrast with frozen-in patterns, and resembles the shape changes during morphogenesis with anisotropic deformations including different types of mechanical instabilities, such as creases, wrinkles, folds, and ridges [20].…”
Section: Introductionmentioning
confidence: 99%
“…Straightforward computation experiments allow us to predict twisting angles and lowest-energy configurations of frame structures. Our theory can be extended to more complex structures [16] and more sophisticated ways of actuation. The shape transformation was studied here for centimeter-scale macroscopic structures but the results are scalable and remain valid for fibers with proportionally reduced geometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…2b), and the orientation of the dividing plane varies along its length. Earlier theoretical studies showed [16,17] that the shape of a Janus ring is governed by the ratio R 0 /R dependent on the extension coefficient, and can exist in multiple states, following discontinuous transitions between shapes with a different number of "petals". The linear stability analysis of an untwisted ring predicts the following numerical values R 0 /R = 3.2, 6.6 and 11.3 for the transitions to shapes with 2, 3, 4 petals, respectively.…”
Section: Janus Ringsmentioning
confidence: 99%
See 2 more Smart Citations